THE EFFECT OF THERMOCYCLING TEST ON THE DIAMETRAL TENSILE STRENGTH VALUE OF BULK FILL RESIN COMPOSITE - Dewi Puspitasari; Andi Lukman; Muhammad Yanuar Ichrom Nahzi (FKG Unlam, 2018)
Background:. Bulk fill resin composite can be applied and light-cured to depths of 4 mms at once. Varying temperature changes in the oral cavity that caused by the comsumption cold or hot food and beverage may cause stress on the resin composite material resulting in restoration failure. Temperature changes at 5°C and 55ºC may decrease the mechanical properties of resin composite, one of which is the diametral tensile strength. Purpose: to analyze the thermocycling test effect using 1500 and 3000 cycles to the diametral tensile strength value. Method: This study was purely experimental post test-only with control design. Twenty four bulk fill resin composite samples were divided into 3 groups, which are control group didn’t tested thermocycling, second group treatment were tested thermocycling 1500 cycles and third group were tested thermocycling 3000 cycles.Diametral tensile strength was tested with universal testiimg machine and analyzed by One Way Annova. Result: mean value of diametral tensile strength bulk-fill resin composite of control group 42.35± 4.08 MPa, group thermocycling 1500 cycles 42.25 ± 2.26 MPa, and group thermocycling 3000 cycles 39,98±1.84 MPa. there are no significant difference in diametral tensile strength values of bulk-fill resin composite between thermocycling test group and control group. Conclusion: Thermocycling test 1500 cycle and 3000 cycles to composite resin not altered the diametral tensile strength value.